Producción y caracterización de películas delgadas de YBaCo4O7+δ por medio de pulverización catódica (sputtering) a presiones altas de oxígeno (2010)
The successful growth of thin films of the novel cobaltite YBaCo4O7+ δ by dc sputtering technique at high oxygen pressure onto r (1012) sapphire substrates is reported. The films were characterized after their structural, morphological, electrical, magnetic and optic properties. X-ray diffraction analysis showed a rather textured growth on the r-sapphire substrates. Despite the high growth temperature (850 ºC) no indication of interface reaction (formation of BaAlO4 or Y2O3) was detected. Measurements of the resistivity as a function of the temperature revealed a semiconductor like character of the as grown films. No indication of possible transitions was observed in the temperature range 300-50 K. The electronic transport mechanism seemed to be dominated by Mott variable range hopping (VRH) conduction. Fitting the VRH model to the experimental data allowed for estimating the density of states of the material at the Fermi level N(EF). The resistivity measured in magnetic fields as strong as 5 T increased notably and positive magnetoresistance values as high as ~60 % at 100 K were obtained. Magnetization measurements showed well defined hysteresis loops at 300 K and 5 K. Nevertheless, the calculate values of the magnetization resulted to be too small for the ferro- or ferrimagnetic states. Raman spectra, in turn, allowed for identifying bands associated with vibrating modes of CoO4 and YO6 in tetrahedral and octahedral configuration, respectively. Additional bands which seemed to stem from Co ions in octahedral configuration were also clearly identified. Finally, measurements of transmittance and reflectance showed intense activity of the films in the infrared region with two well defined energy gaps at 3.7 and 2.2 eV.